Shared Decision-Making and Short-Course Radiotherapy for Operable Rectal Adenocarcinoma: A Patient's Right to Choose. Issue 2 (March 2022) - Col, Nananda F.; Haugen, Vicki
Abstract : BACKGROUND: As new treatment options for colorectal cancer (CRC) emerge, physicians and WOC nurses must be prepared to assist patients to choose care that meets their needs and preferences. A patient with T2N0M0 rectal adenocarcinoma was offered the US current standard of practice; he was not offered alternative treatment options. This case study emphasizes the need to ensure patients are offered all reasonable options for treatment. Shared decision-making is a process that helps patients actively participate in their heath choices rather than exclusively relying on the judgment of a health care provider. CASE: Mr J was a 70-year-old man with operable CRC who sought care at a health care facility in his community. He was offered a single option, based on standard of care for this tumor stage: long-course neoadjuvant chemoradiotherapy followed by surgery and additional chemotherapy. After seeking a second opinion at a cancer care center in another state, Mr J chose to undergo a viable alternative treatment option (short-course radiotherapy, followed by surgery, with chemotherapy contingent on his nodal status post-surgery). No nodal involvement was found post- surgery (T2N0M0) enabling him to avoid postoperative chemotherapy. CONCLUSIONS: This case illustrates the need for all health care providers and carers to regularly engage in shared decision-making when choosing among treatment options. In this case, short-course radiotherapy offered Mr J a shorter duration of treatment and avoided the risk for adverse side effects associated with chemotherapy, resulting in improved health-related quality of life. Initial omission to disclose all treatment options to Mr J may have reflected the preferences of the surgeon, institutional financial pressures, or discomfort with shared decision-making, but it failed to provide him with full range of options, given his diagnosis and tumor stage. All members of the patient's care team, including the WOC nurse, play a pivotal role in ensuring transparency in medical care, including advocating for shared decision-making where patients are made aware of all viable treatments, followed by supporting the patient as they reach a decision.